2018
DOI: 10.1016/j.ymthe.2017.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells Inhibit Inflammatory Lymphangiogenesis in the Cornea by Suppressing Macrophage in a TSG-6-Dependent Manner

Abstract: The cornea is a transparent tissue devoid of blood and lymphatic vessels. However, various inflammatory conditions can cause hemangiogenesis and lymphangiogenesis in the cornea, compromising transparency and visual acuity. Mesenchymal stem/stromal cells (MSCs) have therapeutic potentials in a variety of diseases because of anti-inflammatory properties. Herein, we investigated the effects of MSCs on corneal angiogenesis using a model of suture-induced inflammatory corneal neovascularization. Data demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 45 publications
1
38
0
2
Order By: Relevance
“…Interestingly, macrophages decreased in inflammatory corneas after CXL, which should contribute to the regression of pathologic BVs and LVs in corneas, as macrophages play a key role in the induction of angiogenesis44, 45 and lymphangiogenesis46, 47, 48, 49 under pathological conditions in the cornea and in the maintenance of LVs 50. Furthermore, we also observed significant reduction in CD45 + leukocytes in suture‐induced inflammation in corneas after CXL treatment using riboflavin and UVA.…”
Section: Discussionmentioning
confidence: 53%
“…Interestingly, macrophages decreased in inflammatory corneas after CXL, which should contribute to the regression of pathologic BVs and LVs in corneas, as macrophages play a key role in the induction of angiogenesis44, 45 and lymphangiogenesis46, 47, 48, 49 under pathological conditions in the cornea and in the maintenance of LVs 50. Furthermore, we also observed significant reduction in CD45 + leukocytes in suture‐induced inflammation in corneas after CXL treatment using riboflavin and UVA.…”
Section: Discussionmentioning
confidence: 53%
“…TSG-6 is a pleiotropic immunomodulatory molecule activated rapidly in response to stimulation by several pro-inflammatory cytokines and functions at an early phase of the inflammatory process [38,57,58]. Several lines of evidence suggest that TSG-6 secreted by MSCs can produce anti-inflammatory effects in a wide variety of diseases, such as bronchopulmonary dysplasia [59], diabetic retinopathy [60], corneal injury [44], inflammatory bowel disease [39], renal fibrosis [45], severe acute pancreatitis [61], and other inflammation-associated diseases. In the present study, we showed that intrathecal injection of BMSCs reduced the expression of IL-1β, IL-6, and TNF-α in the ipsilateral spinal cord dorsal horn; meanwhile, BMSCs administration alleviated CCI-induced allodynia and hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%
“…We reasoned that BMSCs exert this analgesic effect by secreting some anti-inflammatory factors. Previous studies have proven that BMSCs can exert a beneficial effect in corneal neovascularization and renal fibrosis by secreting the anti-inflammatory protein TSG-6 [44,45]. Thus, we investigated whether BMSCs exert their therapeutic effect on CCI-induced neuropathic pain by releasing TSG-6.…”
Section: Bmscs Secreted Tsg-6 To Relieve Neuropathic Painmentioning
confidence: 97%
“…Co-incubation of human adipose tissue-derived MSCs suppresses LPS-induced IL-1β secretion from THP-1 monocytes via increasing TSG-6 expression [ 38 ]. Knocking down TSG-6 in MSCs abrogates the inhibitory effects of MSCs on inflammatory neovascularization and monocyte/macrophage infiltration [ 39 ]. The intraarticular injection of MSCs increases TSG-6 expression in joint cartilage and inhibits monoiodoacetate-induced arthritis in rats [ 40 ].…”
Section: Roles Of Tsg-6mentioning
confidence: 99%